The Relative Age Effect in Czech U14 male and female tennis players in 2007-2016 - Kolonicný, V.; Agricola, A.; Bozdech, M.; Zhánel, J. (Studia Sportiva, 2021)
The issue of the Relative Age Effect (RAE) has been long researched, discussed and published both in the academic and coaching community and the number of studies on it in various sports has significantly grown in recent years. The aim of this study was to verify the existence of RAE among Czech male (n = 6552) and female (n = 4131) junior tennis players and to identify possible differences in birthdate effect between male and female players. The research was carried out in players registered in the years 2007-2016 in the U14 age category in Czech Tennis Association (CTA) database; the athletes were divided into three subgroups (`Ranked`, `Top 100`, `Top 10`). Research data were analysed by the methods of descriptive and inferential statistics: relative and absolute frequency, chi-square goodness of fit test () and chi-square test of independence () with the use of effect size (ES index w). A declining tendency of frequencies from Q1 to Q4 between male and female junior players was proven in all three subgroups.In the whole period of 2007-2016, a significant and strong RAE was demonstrated only in the `Top 10` male subgroup (RAE was significant and ES was small or trivial in the other two subgroups). Among the female players, RAE was significant in all three subgroups (ES was small or trivial). Gender differences in RAE in favour of male players were significant in `Top 100` and `Ranked` (ES was small or trivial in all three subgroups). In the short and long term, RAE can have significant implications for the sport development of athletes; both coaches and the professional public can therefore be recommended to pay attention to this issue. The impact of RAE in sport, i.e. the uneven distribution of athletes` birthdates, is more pronounced especially among junior athletes and often significantly affects their sports development and career.